The Influence of Work Motivation, Organizational Commitment and Democratic Leadership Style on Employee Work Discipline: Pengaruh Motivasi Kerja, Komitmen Organisasi dan Gaya Kepemimpinan Demokratis Terhadap Disiplin Kerja Karyawan - Hadi, Heri Lukman; Sari, Dewi Komala (Indonesian Journal of Law and Economics Review, 2023)
This study aims to determine work motivation, organizational commitment and leadership style on work discipline at PT. Premiere wood manufacture in Sidoarjo.This research is a type of quantitative research with hypothesis testing. The sample used in this study were 79 employees of PT. Premiere wood manufacture in Sidoarjo. The analytical tools used in this research are multiple linear regression analysis, determinant coefficient (R2), multiple correlation coefficient (R), f test, t test, and classical assumption test using SPSS version 18 for windows. The primary data in this study were obtained from questionnaires whose measurements used a Likert scale which were tested for validity and reliability.The results of this study prove that work motivation affects work discipline, organizational commitment affects discipline, leadership style affects work discipline and work motivation, organizational commitment and leadership style affects work discipline PT.Premiere Wood Manufacture in Sidoarjo.